2018
DOI: 10.4103/2045-9912.248266
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydrogen on polarization of macrophages and microglia in a stroke model

Abstract: It has been confirmed that inflammation plays an important role in the pathogenesis of ischemic stroke. The polarization of microglia as an important participant in the inflammation following stroke is also found to be involved in stroke. This study aimed to investigate the effects of hydrogen gas on the polarization of macrophages/microglia in vitro. Raw264.7 cells were treated with lipopolysaccharides and then exposed to hydrogen. The microglia were treated with the supernatant from oxygen and glucose depriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…Hydrogen gas has been recognized as one medical gas that has potential in the treatment of cardiovascular disease, inflammatory disease, neurodegenerative disorders, and cancer (17, 60). As a hydroxyl radical and peroxynitrite scavenger, and due to its anti-inflammatory effects, hydrogen gas may work to prevent/relieve the adverse effects caused by chemotherapy and radiotherapy without compromise their anti-cancer potential (as summarized in Table 1 and Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogen gas has been recognized as one medical gas that has potential in the treatment of cardiovascular disease, inflammatory disease, neurodegenerative disorders, and cancer (17, 60). As a hydroxyl radical and peroxynitrite scavenger, and due to its anti-inflammatory effects, hydrogen gas may work to prevent/relieve the adverse effects caused by chemotherapy and radiotherapy without compromise their anti-cancer potential (as summarized in Table 1 and Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory cytokines are a series of signal molecules that mediate the innate immune response, whose dys-regulation may contribute in many diseases, including cancer (5355). Typical inflammatory cytokines include interleukins (ILs) excreted by white blood cells, tumor necrosis factors (TNFs) excreted by macrophages, both of which have shown close linkage to cancer initiation and progression (5659), and both of ILs and TNFs can be suppressed by hydrogen gas (60, 61).…”
Section: Hydrogen Gas Suppresses Inflammatory Cytokinesmentioning
confidence: 99%
“…In recent years, hydrogen has been found to protect against various diseases, mainly by suppressing oxidative stress, inhibiting inflammation, and compromising cell apoptosis (Ohsawa et al, 2007;Sun et al, 2009;Abe et al, 2012). Our previous study has demonstrated that high-concentration hydrogen (HCH) gas (66.7% H 2 and 33.3% O 2 ) can affect the polarization of macrophages in a stroke model (Ning et al, 2018). Whether hydrogen gas is also protective on DILI via inhibiting macrophage polarization is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Cells were harvested at passage four (p4) with 0.25% trypsin, 1 mM EDTA (ThermoFisher) and all experiments were conducted with p5 ASCs. As in previous studies, immortalized macrophage and microglial cell lines were used in order to control the passage number and to avoid the impact of accidentally co-isolated cell populations common in primary culture [ 47 , 48 , 49 , 50 ]. The murine microglial cell line SIM-A9 was purchased from ATCC (Manassas, VA, USA) and maintained in DMEM: F12 culture medium supplemented with 10% heat-inactivated FBS (ThermoFisher), 5% heat inactivated horse serum (HS; ThermoFisher), and 1% anti-mycotic, anti-biotic.…”
Section: Methodsmentioning
confidence: 99%